2015
DOI: 10.1111/ijlh.12347
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and diagnostic testing for hemochromatosis and iron overload

Abstract: Summary Hemochromatosis is the most common genetic disease in northern European populations. Body iron stores progressively increase in most patients, which can lead to cirrhosis of the liver, hepatocellular carcinoma, heart failure, arthritis, and pigmentation. Simple blood tests such as the serum ferritin and transferrin saturation are useful to suggest the diagnosis which can be confirmed in most cases with a simple genetic test for the C282Y mutation of the HFE gene. However, these blood tests are often mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 25 publications
0
73
0
7
Order By: Relevance
“…The second clinical comment concerns the autosomal recessive nature of HFE-related hemochromatosis, so that a heterozygous mutation in HFE gene will not lead to hemochromatosis. It has been reported that among HFErelated hemochromatosis, p.C282Y homozygotes accounts for 95%, p.C282Y/H63D compound heterozygotes and p.H63D homozygotes accounts for 4%, 1%, respectively (Adams, 2015). However, the responsibility of the latter two genotypes in causing hemochromatosis remains highly debated (Porto et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The second clinical comment concerns the autosomal recessive nature of HFE-related hemochromatosis, so that a heterozygous mutation in HFE gene will not lead to hemochromatosis. It has been reported that among HFErelated hemochromatosis, p.C282Y homozygotes accounts for 95%, p.C282Y/H63D compound heterozygotes and p.H63D homozygotes accounts for 4%, 1%, respectively (Adams, 2015). However, the responsibility of the latter two genotypes in causing hemochromatosis remains highly debated (Porto et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that transferrin from rhinoceroses was not as pH-sensitive as human transferrin, and that pH variations were not adequate to accurately measure TIBC in this species, leading to underestimated values. Other methods, such as evaluation of unbound iron binding capacity (UIBC) might be more suitable to calculate Transferrin Saturation in rhinoceroses, as reported in humans [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of serum ferritin and total body iron stores has been clearly established. As the ferritin increases, the risk of significant liver disease rises [5]. It may be elevated in the absence of iron overload, however, and competing comorbidities such as alcoholic liver disease, hepatic steatosis, or viral infections may confuse the diagnosis because of the clinical similarities.…”
Section: Discussionmentioning
confidence: 99%